Low uptake of hepatitis B vaccination among healthcare workers in primary health facilities in Mwanza region, North-Western Tanzania - Ndunguru, Bernada; Wilfred, Diana; Kapesa, Anthony; Kilonzo, Semvua D.; Mirambo, Mariam; Hyera, Fred; Massaga, Fabian (Frontiers in Public Health, 2023)
Background Despite the availability of hepatitis B vaccines (HBV) in Tanzania, their uptake among healthcare workers (HCWs) in high-level facilities, such as tertiary hospitals where the vaccines are available, is low. However, their uptake among HCWs in primary health facilities remains understudied. The lack of this information limits the scaling up of HBV vaccination programs. Methodology A cross-sectional analytical study was conducted between June and July 2022 among HCWs in the Misungwi and Ilemela districts, which were purposefully selected. The sample size was calculated using the Taro Yamane formula, and data were collected using a self-administered questionnaire and analyzed using IBM SPSS® version 25. Results A total of 402 HCWs were recruited, their mean age was 34.9 ± 7.77 years, and only 18% (76/402) reported being fully vaccinated. HCWs in Ilemela showed higher uptake (χ2 = 23.64, df = 1, p = 0.00) of the vaccine than HCWs in Misungwi. Being male (aOR = 2.38, 95% CI 1.28–4.45, p = 0.006), working in an urban setting (aOR = 5.75, 95% CI 2.91–11.35, p = 0.00), and having an employment duration of more than 2 years (aOR = 3.58, 95%CI 1.19–10.74, p = 0.023) were significantly associated with higher odds of vaccination. Moreover, high perceived susceptibility to HBV infection (aOR = 2.20, 95% CI1.02–4.75, p = 0.044) and history of needle prick injuries (aOR = 6.87, 95%CI 3.55–13.26, p = 0.00) were significantly associated with higher odds of HBV vaccination. Conclusion Low uptake of HBV vaccine among HCWs in primary health facilities was observed with a noteworthy difference between rural and urban settings. Therefore, advocacy campaigns and resource mobilization toward the promotion of HBV vaccination in primary health facilities are pivotal.